2016
DOI: 10.1111/tan.12908
|View full text |Cite
|
Sign up to set email alerts
|

Associations between TNFAIP3 gene polymorphisms and systemic lupus erythematosus risk: an updated meta‐analysis

Abstract: In order to determine whether tumor necrosis factor alpha inducible protein 3 (TNFAIP3) gene polymorphisms confers susceptibility to systemic lupus erythematosus (SLE) in ethnically different populations. A meta-analysis was conducted to examine the association between TNFAIP3 polymorphisms and susceptibility to SLE. A systematic literature search was conducted to identify all relevant studies. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the strength of the association. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Two tightly linked variants, rs719149 and rs719150, associated with lower levels of TNFAIP3 in AxSpA cases only but not controls ( p  = 0.016 for SpA status). Variants rs5029937, rs5029939, and F127C have previously been reported to associate with RA and SLE and showed a trend toward lower levels in this study (45, 46). However, none of the individual variants identified were statistically significant following correction for multiple variant testing.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Two tightly linked variants, rs719149 and rs719150, associated with lower levels of TNFAIP3 in AxSpA cases only but not controls ( p  = 0.016 for SpA status). Variants rs5029937, rs5029939, and F127C have previously been reported to associate with RA and SLE and showed a trend toward lower levels in this study (45, 46). However, none of the individual variants identified were statistically significant following correction for multiple variant testing.…”
Section: Resultssupporting
confidence: 61%
“…Some of the TNFAIP3 variants found in our population have been reported in other diseases: rs5029937 and F127C with RA and SLE, rs5029939 with SLE and systemic sclerosis, and F127C and rs610604 with psoriasis (45, 46, 60, 61). However, despite the increasing implication of TNFAIP3 in multiple autoimmune and inflammatory diseases, little information is available regarding how TNFAIP3 variants modulate gene expression.…”
Section: Discussionsupporting
confidence: 58%
“…Sequencing the exon regions of TNFAIP3 revealed two SNPs in close proximity to the OTU catalytic site. While rs2230926:T>G has been well-studied in the context of autoimmune diseases [39,49,50], rs146534657:A>G is poorly-characterized with only one report linking it to poor outcome among Chinese RA patients [34]. The function of this SNP in altering the amino acid directly adjacent to the catalytic cysteine within the OTU and its prevalence among Hispanics highlight clinical implications among this population.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study from 10 casecontrol research revealed that rs5029937 polymorphism increased the risk of RA among Caucasians (21). Furthermore previous studies demonstrated that this variant is associated with SLE in Europeans and Asian populations (24,32). In the present study, we assessed the possible association between SNP rs5029937 (G>T) in the TNFAIP3 gene with RA risk in the Iranian population for the first time.…”
Section: Introductionmentioning
confidence: 89%